Five tools for five challenges: designing a virtual breakout - Castillo-Rodríguez, Cristina Milagrosa; Torrado Cespón, Milagros (UMA Editorial, 2020)
The educative breakout is a type of microgamification implemented in the classroom and is aimed at generating significant learning in students. This significant learning is achieved by means of activities and tasks designed in the form of challenges students have to solve. However, today we have witnessed to a real change of context, as virtuality has been given priority over the face-to-face context so as to adapt to new settings and scenarios in education without impoverishing students’ learning. In this line is where we present the work and the Project GAME-EDU. We have collected a series of tools to design virtual challenges in the framework of two groups, B and C, of a subject taught in English and Spanish, respectively. Thus, in this work we will describe the tools used to elaborate the challenges for the virtual breakout and will expose the ranking of favourite tools of participants from both groups.
Keywords: Aplicaciones informáticas - Enseñanza; Greakout; University; Active methodology; Gamification; Virtual challenges